Influence Occupational Health Safety and Work Discipline on Employee Productivity at the Energy and Mineral Resources Department of South Sumatra - Rio Kurniawan; Tri Darmawati; Santi Puspita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study aims to determine how the productivity of employees of the Energy and Mineral Resources Agency is measured based on health safety and work discipline. Research Methodology: Quantitative methods were used, and the data collection techniques used in this study were observation, documentation, and questionnaire distribution. While the data analysis techniques in the study were analyzed using normality test, multicollinearity test, heroskedacity test, multiple linear analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing which consists of t test (partial) and f test (simultaneous). Results: The results of the hypothesis testing concluded that partial occupational health safety has a positive and significant effect on employee productivity at the Energy and Mineral Resources Office of South Sumatra Province. Work discipline had a positive and significant effect on employee productivity at the Energy and Mineral Resources Office of South Sumatra Province. Simultaneously, occupational health safety variables and work discipline had a positive and significant effect on employee productivity at the Energy and Mineral Resources Office of South Sumatra Province. Limitations: The research was conducted only at the Energy and Mineral Resources Office of South Sumatra Province and only included occupational health safety variables, work discipline, and employee productivity. Contribution: The results of this study are expected to contribute to increasing labor productivity, as well as provide useful references for other researchers and UPGRI in increasing knowledge and abilities in the world of labor.